Ketegangan antara Independensi Kekuasaan Kehakiman dan Politik Pengisian Hakim Konstitusi di Indonesia - Sandra Leoni Prakasa Yakub; Rengga Kusuma Putra; Lita Tyesta Addy Listya Wardhani; Fifiana Wisnaeni; Dian Karisma (Universitas Kapuas, 2026)
The appointment mechanism of constitutional court judges represents a critical intersection between judicial independence and democratic legitimacy. In Indonesia, the tripartite nomination model involving the President, the House of Representatives, and the Supreme Court was originally designed to embody checks and balances. However, recent institutional developments raise concerns regarding structural vulnerabilities within this design. This article examines whether Indonesia’s appointment model adequately safeguards judicial independence or instead generates institutional dependency. Employing normative juridical analysis combined with a functional comparative approach, the study compares Indonesia’s system with those of Germany and South Korea, both of which operate centralized constitutional review mechanisms. This article argues that Indonesia’s fragmented yet majoritarian appointment structure structurally produces appointment dependency, distinguishing it from the institutionalized political constraint models found in Germany and South Korea. While political involvement in judicial selection is not inherently incompatible with judicial independence, the absence of supermajoritarian consensus requirements and structured public scrutiny increases the risk of majoritarian capture. The article proposes a reconstruction of Indonesia’s appointment design through the introduction of qualified majority requirements and institutionalized public deliberation mechanisms. Such reforms aim to recalibrate the balance between democratic legitimacy and judicial autonomy within Indonesia’s constitutional framework.